Researching Internet Governance Methods, Frameworks, Futures - DeNardis, Laura; Cogburn, Derrick; Levinson, Nanette S.; Musiani, Francesca (Information Policy, 2020)
A multidisciplinary book that takes internet governance research as a research subject in its own right, discussing methods and conceptual approaches. The design and governance of the internet has become one of the most pressing geopolitical issues of our era. The stability of the economy, democracy, and the public sphere depend on the stability and security of the internet. Revelations about election hacking, facial recognition technology, and government surveillance have gotten the public's attention and made clear the need for scholarly research that examines internet governance both empirically and conceptually. In this volume, scholars from a range of disciplines consider research methods, theories, and conceptual approaches in the study of internet governance. The contributors show that internet governance is not only about governments; it is enacted through technical design, resource coordination, and conflicts at various invisible control points. They discuss such topics as the emergence of "internet governance" as an area of academic study and a real-world policy arena; the scholarly perspectives of STS, the law, computer science, and political science; the use of big data and text mining in internet governance studies; and cybersecurity. Contributors Farzaneh Badiei, Davide Beraldo, Sandra Braman, Ronald J. Deibert, Dame Wendy Hall, Jeanette Hofmann, Eric Jardine, Rikke Frank Jørgensen, Aastha Madaan, Stefania Milan, Milton Mueller, Kieron O'Hara, Niels ten Oever, Rolf H. Weber